36.4k views
4 votes
Determine the response to input x[n]=(2)ⁿ u[−n−1] of the anti-causal system described by given the difference equation:

y[n]−(3/4)y[n−1]+(1/8)y[n−2]=x[n]+0.25x[n−1]

User Sur Max
by
7.4k points

1 Answer

6 votes

Final answer:

To determine the response to input x[n]=(2)ⁿ u[−n−1] of the anti-causal system described by given the difference equation: y[n]−(3/4)y[n−1]+(1/8)y[n−2]=x[n]+0.25x[n−1], the difference equation needs to be solved using the given input.

Step-by-step explanation:

To solve for the output of an anti-causal system given the input x[n]=(2)^n u[-n-1] and the difference equation, one would typically employ the Z-transform. ;To determine the response to input x[n]=(2)ⁿ u[−n−1] of the anti-causal system described by given the difference equation: y[n]−(3/4)y[n−1]+(1/8)y[n−2]=x[n]+0.25x[n−1], we need to solve the difference equation using this input.

Step 1: Substitute the given input x[n]=(2)ⁿ u[−n−1] into the difference equation.

Step 2: Simplify and solve for y[n].

The detailed solution involves substitution and algebraic manipulation.

User Paul Stelian
by
8.0k points